Endothelial-dependent Mechanisms Regulate Leukocyte Transmigration: A Process Involving the Proteasome and Disruption of the Vascular Endothelial–Cadherin Complex at Endothelial Cell-to-Cell Junctions - Allport, Jennifer R. (The Rockefeller University Press, 1997)
Although several adhesion molecules expressed on leukocytes (β1 and β2 integrins, platelet endothelial cell adhesion molecule 1 [PECAM-1], and CD47) and on endothelium (intercellular adhesion molecule 1, PECAM-1) have been implicated in leukocyte transendothelial migration, less is known about the role of endothelial lateral junctions during this process. We have shown previously (Read, M.A., A.S. Neish, F.W. Luscinskas, V.J. Palambella, T. Maniatis, and T. Collins. 1995. Immunity. 2:493–506) that inhibitors of the proteasome reduce lymphocyte and neutrophil adhesion and transmigration across TNF-α–activated human umbilical vein endothelial cell (EC) monolayers in an in vitro flow model. The current study examined EC lateral junction proteins, principally the vascular endothelial (VE)–cadherin complex and the effects of proteasome inhibitors (MG132 and lactacystin) on lateral junctions during leukocyte adhesion, to gain a better understanding of the role of EC junctions in leukocyte transmigration. Both biochemical and indirect immunofluorescence analyses of the adherens junction zone of EC monolayers revealed that neutrophil adhesion, not transmigration, induced disruption of the VE–cadherin complex and loss of its lateral junction localization. In contrast, PECAM-1, which is located at lateral junctions and is implicated in neutrophil transmigration, was not altered. These findings identify new and interrelated endothelial-dependent mechanisms for leukocyte transmigration that involve alterations in lateral junction structure and a proteasome-dependent event(s).